2000
DOI: 10.4049/jimmunol.165.12.7270
|View full text |Cite
|
Sign up to set email alerts
|

Highly Autoproliferative T Cells Specific for 60-kDa Heat Shock Protein Produce IL-4/IL-10 and IFN-γ and Are Protective in Adjuvant Arthritis

Abstract: Previously we have shown that T cell responses to the mycobacterial 60-kDa heat shock protein (hsp60) peptide M256–270 mediated protection against adjuvant arthritis in Lewis rats. We have demonstrated now that M256–270-primed T cells become highly reactive to naive syngeneic APC upon repetitive restimulation in vitro with peptide M256–265, comprising the conserved core of peptide M256–270. These autoproliferative responses in the absence of added Ag were MHC class II restricted and resulted in the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 54 publications
2
42
1
Order By: Relevance
“…Although the precise nature of the peptide(s) recognized by T cells in this setting is unknown, it was previously established that MHC class II molecules bind self peptides in absence of exogenous antigens [9] and that expansion of self-reactive MHC class II-restricted T cells is driven by auto-antigens derived from apoptotic cells present in the coculture [10;11]. The fact that regulatory T cells generated during the autologous reaction proliferated and produced cyto- kines of the effector type is consistent with several recent observations [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 73%
“…Although the precise nature of the peptide(s) recognized by T cells in this setting is unknown, it was previously established that MHC class II molecules bind self peptides in absence of exogenous antigens [9] and that expansion of self-reactive MHC class II-restricted T cells is driven by auto-antigens derived from apoptotic cells present in the coculture [10;11]. The fact that regulatory T cells generated during the autologous reaction proliferated and produced cyto- kines of the effector type is consistent with several recent observations [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 73%
“…While addressing hybridoma recognition of the endogenous Hsp70, we found that some of the hybridoma clones were increasingly activated after incubation with HS APC. In line with these data, our previous study in rats showed that Hsp60-specific Tcells recognized up-regulation of cellular Hsp60 in the APC (Paul et al 2000). The mC1b peptide from mouse HspA1A has been frequently eluted from MHC class II (Halder et al 1997;Chicz et al 1993;Dengjel et al 2005).…”
Section: Discussionsupporting
confidence: 69%
“…IL-10 and TGF␤1 are immunomodulatory cytokines capable of inhibiting experimental arthritis (21)(22)(23). Indeed, T cells reactive with self-HSP60 have been previously shown to control AA (24). Inflammation up-regulates HSP60 expression in lymphocytes (25), macrophages (26), and synovial cells (27,28).…”
Section: Discussionmentioning
confidence: 99%